Resveratrol protects against copper and iron toxicity in Drosophila melanogaster - Osaretin Godwin Igharo; Lucky Osemu EBALUEGBEIFOH; Godwin Aigbedo AIKPITANYI-IDUITUA; Henry Uzor OSHILONYAH; Idris Babatunde MOMODU (Universa Medicina, 2023)
BackgroundCopper (Cu) and iron (Fe) are essential trace elements that when in excess are capable of causing cytotoxic effects leading to lipid peroxidation and promoting oxidative stress. Resveratrol (RES) is a natural polyphenol with antioxidant and anti-inflammatory properties. This study was carried out to evaluate the protective role of RES in Fe and Cu sulphate-induced oxidative stress in Drosophila melanogaster. MethodsAdult wild type flies were fed Cu2+ and Fe2+ (1 mM each) and/or RES (30 and 60 mg/kg diet) for 7 days. Survival, negative geotaxis and emergence rate were evaluated by daily recording of fruit fly mortality and final analysis. Fruit flies were anaesthetized using CO2 gas, homogenized and centrifuged at 4,000 rpm for 10 minutes at 4 °C. Aliquots of the supernatants were used for the estimation of biochemical markers using spectrophotometry. ResultsFruit flies co-treated with FeSO4 + CuSO4 (1 mM each) + RES (30 and 60 mg/Kg) significantly elevated H2O2, NO, lipid peroxidation, acetylcholinesterase as well as GSH, GST, catalase and total thiols (p<0.05) compared with the Cu2+ + Fe2+ (1mM each) treated group. Flies co-treated with FeSO4 + CuSO4 (1mM each) + RES (30 and 60mg/Kg) also had significantly improved (p< 0.05) eclosion and climbing rates compared with the Cu2+ + Fe2+ (1mM each) treated group. ConclusionThis study demonstrated that RES reduced Cu2+ and Fe2+-induced radical generation in D. melanogaster and improved the antioxidant buffering capability of the flies. Therefore, RES could be used in management of disorders involving oxidative stress.